Textbook of veterinary physiology - Cunningham, James G. (Elsevier, 2007)
Now with full-color illustrations, this easy-to-follow text takes the vast subject of physiology and focuses on concepts most important to the practice of veterinary medicine. It includes coverage of physiopathology and clinical problem-solving techniques, making this a practical resource for any practice. The book's logical, body-system organization makes it easy to find specific information. This edition includes a new chapter on cancer and a new section on the immune system.